SMART MITIGATION LEARNING : INOVASI PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BUMISANA (BUKU SAKU MITIGASI BENCANA) BERBANTUAN AUGMENTED REALITY (AR) UNTUK MENINGKATKAN DISASTER LITERACY AWARENESS SISWA SEKOLAH DASAR DI JAKARTA - Indah Wardatussa'idah; Taofik; Rahmawati; Anggit Aruwiyantoko; Chrisnaji Banindra Yudha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Jakarta is one of the regions in Indonesia with a high vulnerability to various natural disasters. Conversely, the level of disaster literacy awareness among elementary school students remains relatively low due to the limitations of interactive and contextual learning media. This study aims to develop and test the feasibility of "BUMISANA" (Buku Saku Mitigasi Bencana / Disaster Mitigation Pocket Book), an innovative interactive learning media based on Augmented Reality (AR) specifically designed to enhance disaster literacy awareness among elementary school students in Jakarta. The research method employed is Research and Development (R&D) using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects involved elementary school students in the DKI Jakarta area. Data collection was conducted through validation questionnaires from material and media experts, observation sheets, and tests (pre-test and post-test) to measure the increase in students' disaster literacy. The research results show that: (1) The theoretical validity of the media reached an average of 96.81% with a Very Valid criterion based on assessments from content experts (98.21%), language experts (97.22%), and media experts (95.00%); (2) The empirical practicality of the media obtained an average cumulative score of 91.17% with a Very Practical criterion, including One-to-One trials (96.4%), Small Group trials (92.0%), and Field Tests (90.0%); and (3) The effectiveness of the media proved to trigger an increase in the average student comprehension score from 77.59 (pretest) to 81.55 (posttest), with 82.76% of the total student population experiencing positive score improvements. In conclusion, the AR-assisted BUMISANA media is considered very valid, practical, and effective to use as an interactive learning medium to improve disaster literacy among elementary school students.